Look to windward - Banks, Iain 1954-2013 (Orbitt Books, 2000)
It was one of the less glorious incidents of a long-ago war. It led to the destruction of two suns and the billions of lives they supported. Now, eight hundred years later, the light from the first of thos ancient deaths has reached the Culture's Orbital called Masaq'. For the Hub Mind, an overseer of the massive bracelet world, its arrival is particularly poignant. But it may still be eclipsed by events from the Culture's more recent past.
Keywords: Utopies - Science-fiction; Vie extraterrestre - Science-fiction; Life on other planets -- Fiction; Space warfare -- Fiction; Utopias -- Fiction; Science fiction